Fluorescent boron Schiff bases dyes for staining silk fibroin: Green synthesis, structural characterization, DFT, and photophysical properties*. (7th December 2018) - Molina‐Paredes, Areli A.; Jiménez‐Pérez, Víctor M.; Lara‐Cerón, Jesús A.; Moggio, Ivana; Arias, Eduardo; Santillán, Rosa; Sánchez, Mario; Saucedo‐Yañez, Alma; Muñoz‐Flores, Blanca M.
Abstract : Five novel organoboron complexes were synthesized in just 15 min via microware irradiation, by one pot multicomponent reactions between diverse aryl aldehydes with benzoylhydrazide, or 4‐nitrobenzoylhidrazine and diphenyl boronic acid, in a 1:1:1 ratio in benzene. The products were characterized by 1 H, 13 C, 11 B NMR, UV, IR, spectroscopy and high‐resolution mass spectrometry (HRMS). The molecular structure was also determined by single‐crystal X‐ray diffraction for two complexes, which showed the tetra‐coordination of the boron atoms giving rise to distorted tetrahedral molecular geometry with a strong intermolecular C‐H···π interactions. In spite of the low quantum yields exhibited by the series in solution, some complexes stained uniformly the silk fibroins emitting enough fluorescence to allow its characterization by confocal microscopy. Boron as chelate center of the five complexes resulted not to be toxic for B16F10 cells, these compounds are appropriate for their used in medical applications. Abstract : Five novel organoboron complexes were synthesized via microwave irradiation and one pot multicomponent reactions. The products were characterized by 1 H, 13 C, 11 B NMR, UV, IR, and HRMS. Molecular structure was determined by single‐crystal X‐ray diffraction for two complexes, which showed the tetra‐coordination of boron atoms giving rise to distorted tetrahedral molecular geometry. Complexes were used to produce luminescent silk fibroin and were characterized by confocal microscopy. Cell viability assays showed that the compounds are suitable for use in medical applications.